EFL Students’ Pronunciation in Indonesia and Thailand: Exploring Differences and Errors - Tusino, Tusino (Universitas PGRI Semarang, 2026)
Studies comparing language proficiency and pronunciation errors are under-researched in EFL environments. The present study aims to explain the differences and pronunciation errors found among students from Indonesia and Thailand. This quantitative study employed a comparative design. The participants were sixty-two public secondary schools in Indonesia and Thailand. The research instruments used were pronunciation tests and closed-ended questionnaires. Data were analyzed using descriptive and inferential methods. The results showed a significant difference in English pronunciation between the two groups of students: Indonesian and Thai. The Indonesian students made errors in the pronunciation of specific vowels and consonants. In contrast, the Thai learners could not correctly pronounce specific vowels and consonants. Language exposure, the learners’ native language, language anxiety, and phonological knowledge were identified as major factors influencing pronunciation errors. The findings indicate that Indonesian and Thai students exhibit different patterns of English pronunciation errors, influenced by linguistic and non-linguistic factors.